Association of serum iron with all-cause mortality and cardiovascular mortality in the cardiovascular patients: a retrospective cohort study based on the NHANES 1999–2018 - Lu, Jing; Ma, Zhen; Zhang, Xiaoxue; Zhong, Wenhao; Zou, Yunzeng; Yuan, Jie (Frontiers in Cardiovascular Medicine, 2024)
BackgroundCardiovascular disease (CVD) is one of the leading global causes of death, and serum iron (SI) levels may be associated with the mortality of CVD. However, there is still a knowledge gap regarding the relationship between SI and mortality in the CVD population.MethodsAn analysis was conducted utilizing data from the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2018. In our study, SI was used as the independent variable, and the mortality of the CVD patients was considered as the outcome. Kaplan–Meier curves, multivariable Cox proportional hazards model, and restricted cubic spline were employed to examine the association between SI and all-cause mortality and cardiovascular mortality in CVD patients. Subgroup analysis was also carried out based on age, sex, weight, hypertension, Type 2 diabetes mellitus, and smoking status.ResultsA retrospective cohort study design was utilized, incorporating data from 1,903 CVD patients with an average age of 64.29 years. Kaplan–Meier survival analysis demonstrated significant differences in all-cause mortality and cardiovascular mortality among the CVD patients based on quartiles of SI. Following multivariable adjustment, lower SI was associated with an increased risk of all-cause and cardiovascular mortality in CVD patients. The highest quartile of SI exhibited a 43% reduction in all-cause mortality (HR = 0.57, 95% CI: 0.45–0.72) and a 74% reduction in cardiovascular mortality (HR = 0.26, 95% CI: 0.16–0.43) when compared to the lowest quartile. Restricted cubic spline showed a nonlinear relationship between SI and all-cause mortality and a linear relationship between SI and cardiovascular mortality. Additionally, the inverse relationship between SI levels and outcomes in the CVD patients remained consistent in subgroup analysis.ConclusionHigher SI is associated with a decreased risk of all-cause and cardiovascular mortality in CVD patients. Our results emphasize the importance of iron supplementation for this particular group.